México-Canadá: el camino hacia una sociedad estratégica - Studer, Isabel; Contreras, Talia (Revista Mexicana de Política Exterior, 2022)
Canada and Mexico have the opportunity to build a strategic partnership that contributes to the creation of a safer, more prosperous North America. Although the bilateral relationship has certainly progressed over the last 15 years, it lacks a sense of mutual cooperation that favors the interests of the region as a whole. What’s more, it would appear that Canada and Mexico have systematically avoided such a strategy, thereby diminishing the importance of their bilateral ties. According to Studer and Contreras, several factors are generally listed as impediments to a more solid trilateral agenda, the main ones being asymmetries between the three countries, particularly between Mexico and its northern neighbors, and failure on the part of the two more developed partners to balance the scales. And since a safer, more prosperous, more competitive North America depends on closing these regional gaps, it is in the interests of all three countries to cooperate in this area. That said, the current situation —a superpower occupied with multiple global affairs and distracted by a polarized political environment on the home front— requires that the smaller partners seize the initiative. Studer and Contreras believe Canada can actively contribute to Mexico’s development, while continuing to serve its own interests and those of the region. The challenge resides in finding new ways of exploiting their complementary facets to form an authentic strategic partnership that constitutes a “win-win” strategy for North America. The shoring up of regional industries; projects to boost the competitiveness of the region’s workforce; coordinated actions to address the issues of energy security and climate change; a common framework to tackle security concerns like terrorism and drug trafficking; and the strengthening of Mexico’s democratic capacities. These are just a few of the areas in which the strategic interests of Mexico and Canada coincide and on which a partnership that benefits each country and the region as a whole could be built.